2018
DOI: 10.5578/fmbd.67502
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Gravity Anomalies based on Recent High-Degree Global Models

Abstract: The Earth system generates different phenomena that are observable at the surface of the Earth such as: Mass deformations and displacements leading to plate tectonics, earthquakes, and volcanism. The dynamic processes associated with the interior, surface, and atmosphere of the Earth affect the three pillars of geodesy: Shape of the Earth, its gravity field, and its rotation. Geodesy establishes a characteristic structure in order to define, monitor, and predict of the whole Earth system. The traditional and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Figure 6 refers to a vertical gradient of normal gravity as an approximation in which a gravity measurement point, which is almost never placed on the reference ellipsoid's surface, is adjusted according to geophysical corrections [88,89]. The details regarding the distribution of vertical gravity values over Venezuela, Trinidad, and Tobago showed that the lowest values (below −100 mGal) mostly correspond to the extreme amplitude of topographic changes, e.g., the abrupt borders between the mountains/hills and the margins of the bathymetric depression, while the highest values (over 100 mGal) were detected on the tops of the mountains, which corresponded well with the local geomorphology of the region.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 refers to a vertical gradient of normal gravity as an approximation in which a gravity measurement point, which is almost never placed on the reference ellipsoid's surface, is adjusted according to geophysical corrections [88,89]. The details regarding the distribution of vertical gravity values over Venezuela, Trinidad, and Tobago showed that the lowest values (below −100 mGal) mostly correspond to the extreme amplitude of topographic changes, e.g., the abrupt borders between the mountains/hills and the margins of the bathymetric depression, while the highest values (over 100 mGal) were detected on the tops of the mountains, which corresponded well with the local geomorphology of the region.…”
Section: Resultsmentioning
confidence: 99%
“…The gravity anomaly residuals and the total number of selected points were used to compute the RMSE. The Root Mean Square Error, RMSE was computed using the formula given by Yilmaz and Kozlu (2018);…”
Section: Validation Of the Interpolated Gravity Datamentioning
confidence: 99%
“…Here, the accuracy of the model varies inversely to the computed value of the RMSE [21]. The Root Mean Square Error, RMSE index used for the computation of the geometric geoid model accuracy as given by Yilmaz and Kozlu [22] is…”
Section: Accuracy Of the Modelmentioning
confidence: 99%